1978
DOI: 10.1037/0096-1523.4.4.545
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the reader's skill and the difficulty of the text on the perceptual span in reading.

Abstract: Development of the perceptual span in reading was investigated by varying the availability of graphic information in the periphery of vision. Low-ability eighth-grade readers, high-ability eighth-grade readers, and skilled adult readers read texts presented in a normal prose format, with a single space between words, and texts typed with 13 letter spaces between words. It was found that removing peripheral information by wide spacing improved comprehension for low-ability eighth graders but did not affect thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

1980
1980
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…Their performance for RSVP reading presumably was not as good as that for page reading. In fact, Patberg and Yonas (1978) have discussed the possibility that skilled reading may be disrupted to a greater degree than less skilled reading by tasks requiring modifications of well-practiced techniques. However, a more efficient system would also be expected to be more flexible and independent of input methods.…”
Section: Discussionmentioning
confidence: 99%
“…Their performance for RSVP reading presumably was not as good as that for page reading. In fact, Patberg and Yonas (1978) have discussed the possibility that skilled reading may be disrupted to a greater degree than less skilled reading by tasks requiring modifications of well-practiced techniques. However, a more efficient system would also be expected to be more flexible and independent of input methods.…”
Section: Discussionmentioning
confidence: 99%
“…Patberg and Yonas (1978) conducted a study in which good and poor readers read passages of normal text and passages typed with 13 spaces between each adjacent pair of words. By spacing the words so widely apart, they reduced the amount of peripheral information that could be acquired from one word while the…”
Section: Discussionmentioning
confidence: 99%
“…The span of perception was determined by establishing the size of the window at the point when eye movements were disrupted. Patberg and Yonas (1978) and Patberg (Note 2) used a simplified version of this principle i.e., eliminating the peripheral information in a developmental study. Again, the hypothesis was that the better reader would be more affected by the loss of peripheral information than the poorer reader.…”
Section: Span Of Letter Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comprehension is evidently unaffected by the absence of this information. An experiment by Patberg and Yonas (1978) presented readers with either normal text or text that permitted a perceptual span of only one word (there were 13 letter spaces between words). For skilled readers, they found that, while the one-word presentation slowed reading speed, comprehension was unaffected compared with normal text.…”
Section: Discussionmentioning
confidence: 99%